Finite Element of Static Contact between Rolling Element and Raceway of Cageless Ball Bearing - ZHAO Yan-ling; WANG Ming-zhu; HOU Xin-xin; QIN Sheng (Journal of Harbin University of Science and Technology)
At present, scholars at home and abroad have paid attention to the improvement of bearing capacity and lightweight due to the removal of cage, but the theoretical research on rolling element contact is less.The principle of adding local variable speed surface to outer ring raceway to change the contact state between rolling element and raceway is proposed.Based on Hertz theory, the contact force and contact stress model between rolling element and raceway are established, and the influence factors of variable speed surface parameters on contact state between rolling elements and raceway are analyzed.Through finite element numerical simulation, the rolling element and raceway, rolling element and variable speed surface are simulated and obtained. The change law of contact stress and strain of the rolling element in and out of the variable speed surface is determined by quantifiable parameters, and the wear test of the designed variable speed surface is carried out with the physical prototype to verify the correctness of the theory The results show that the contact force between the rolling body and the variable speed surface edge is greater than that at the middle position, and the adjacent rolling body is in noncontact state when rolling through the variable speed surface.This study provides a theoretical basis for the dynamic wear of no cage ball bearings.